2016
DOI: 10.1002/uog.14871
|View full text |Cite
|
Sign up to set email alerts
|

Extracardiac anomalies in prenatally diagnosed heterotaxy syndrome

Abstract: Objective To assess the incidence and impact of extracardiac anomalies on the prognosis of fetuses with heterotaxy syndrome.Methods All fetuses diagnosed with heterotaxy syndrome by three experienced examiners over a period of 14 years (1999-2013)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 25 publications
4
53
1
Order By: Relevance
“…A total of 2037 articles were identified from the electronic search, of which 134 were assessed with respect to their eligibility for inclusion (Table S2) and a total of 16 studies were eventually included in the systematic review ( Figure 1, Table 1) 12,14,[25][26][27][28][29][30][31][32][33][34][35][36][37][38] . These 16 studies included 647 fetuses with a prenatal diagnosis of isomerism, of which LAI was confirmed at birth in 61.7% (95% CI, 57.8-65.4%) and RAI in 38.3% (95% CI, 34.6-42.2%).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2037 articles were identified from the electronic search, of which 134 were assessed with respect to their eligibility for inclusion (Table S2) and a total of 16 studies were eventually included in the systematic review ( Figure 1, Table 1) 12,14,[25][26][27][28][29][30][31][32][33][34][35][36][37][38] . These 16 studies included 647 fetuses with a prenatal diagnosis of isomerism, of which LAI was confirmed at birth in 61.7% (95% CI, 57.8-65.4%) and RAI in 38.3% (95% CI, 34.6-42.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of lung lobulation patterns is difficult in the absence of effusion in the pleural space. Liver, stomach, and gall bladder may be in either position (the solitus or inversus) and viserocardiac ambiguity is not a consistent feature . In contrast, cardiovascular abnormalities are more prevalent in antenatally detected cases …”
Section: Discussionmentioning
confidence: 99%
“…Among extracardiac defects, gut malrotation and biliary atresia are the most common anomalies, reported in about 40–50% of cases . Gottschalk et al reported biliary atresia as the most important extracardiac contributing factor to the postnatal prognosis. In our case, the nonvisualization of the gallbladder could suggest biliary atresia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations